Economik and management science in the oil and gas industry of Ukraine: state, drawbacks, ways of improving - Петренко, В. П. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
1